2000
DOI: 10.1046/j.1460-9568.2000.00903.x
|View full text |Cite
|
Sign up to set email alerts
|

Different forms of LTD in the CA1 region of the hippocampus: role of age and stimulus protocol

Abstract: In this study, we have investigated the developmental range over which different stimulus protocols induce long-term depression (LTD). Low-frequency stimulation (LFS; 900 stimuli, 1 Hz) produced LTD in hippocampal slices from rats younger than approximately 40 days old, but not in animals aged between approximately 40 days and 16 weeks. We demonstrate, however, that different stimulus protocols can result in LTD in the adult hippocampus. Whilst one paired-pulse low-frequency stimulus protocol [PP-LFS; 50 ms pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
138
3

Year Published

2002
2002
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 189 publications
(156 citation statements)
references
References 35 publications
(47 reference statements)
15
138
3
Order By: Relevance
“…Although several groups have shown that PKC activity is necessary for mGluR LTD in several brain regions, including CA1 (3,15), it was also demonstrated that high-frequencyinduced PKC activation inhibited synaptically induced mGluR LTD in the dentate gyrus (16,17), demonstrating the dependence of mGluR LTD metaplasticity on PKC. The location of mGluR LTD activation and maintenance has also been the subject of debate with some studies implicating a presynaptic expression mechanism and others implicating a postsynaptic one (5,13,21). To study the dynamics and location of this possible interaction, it was necessary to isolate the effects of m1-mediated signaling on the response to stimulating mGluRs by removing m1 receptors.…”
Section: Discussionmentioning
confidence: 99%
“…Although several groups have shown that PKC activity is necessary for mGluR LTD in several brain regions, including CA1 (3,15), it was also demonstrated that high-frequencyinduced PKC activation inhibited synaptically induced mGluR LTD in the dentate gyrus (16,17), demonstrating the dependence of mGluR LTD metaplasticity on PKC. The location of mGluR LTD activation and maintenance has also been the subject of debate with some studies implicating a presynaptic expression mechanism and others implicating a postsynaptic one (5,13,21). To study the dynamics and location of this possible interaction, it was necessary to isolate the effects of m1-mediated signaling on the response to stimulating mGluRs by removing m1 receptors.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies suggest that mGluR-LTD is only observed at early developmental time periods in area CA1 (P7-P11) (Bolshakov and Siegelbaum, 1994;Overstreet et al, 1997). However, others indicate that mGluR-LTD is restricted to adult animals (Kemp et al, 2000). There is general agreement that mGluR-LTD is induced postsynaptically (Bolshakov and Siegelbaum, 1994;Oliet et al, 1997;Watabe et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…To examine whether caveolin-1 is required for mGluR-independent forms of LTD, we examined NMDAR-LTD at CA1 synapses of Cav1 −/− mice. We delivered low-frequency stimulation (LFS; 1,200 pulses at 1 Hz) to Schaffer collateral axons and recorded fEPSCs in area CA1 (35)(36)(37). LFS induced robust depression of fEPSPs in slices from both WT and Cav1 −/− mice, as assessed 35-40 min after stimulation (WT depression to 83 ± 5% of baseline, n = 9; Cav1 −/− depression to 79 ± 4% of baseline, n = 8; P > 0.05 Cav1 −/− vs. WT, P < 0.001 Cav1 −/− or WT vs. baseline; Fig.…”
mentioning
confidence: 99%